(8RS)‐4‐Amino‐6‐(4‐chlorophenyl)‐8‐(2, 4‐dichlorothiazol‐5‐yl)‐8, 9‐dihydro‐7H‐pyrimido[4, 5‐b][1, 4]diazepine N, N‐dimethylformamide monosolvate: sheets built from N—H...N and C—H...O hydrogen bonds. Issue 6 (6th May 2014) - Ramírez, Juan; Insuasty, Braulio; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the title compound, C16H11Cl3N6S·C3H7NO, the seven‐membered ring adopts a conformation which is close to the twist‐boat form. The molecular components are linked into sheets by a combination of two N—H...N hydrogen bonds and two C—H...O hydrogen bonds. Comparisons are made with other aminopyrimidine derivatives.